The desert : lands of lost borders - Welland, Michael, 1946- (London : Reaktion Books, 2015)
Lands of extremes, contrasts and constant change, deserts cover a quarter of our planet's land area and are home to some half a billion people. 'The desert' as an idea has long captured the Western imagination, but too often in ways that fail to grasp the true scope and diversity of these spaces. Misconceptions and misrepresentations also abound about the realities of the lives of people for whom the desert is home. Deserts are landscapes of the mind as much as physical realities - they are places of metaphor and myth. For the outsider, stories of the desert are about the exotic and the hostile - about adventures into unknown territory. Few of us consider the perspectives of those who live in and navigate the desert each day. This book attempts to bridge the gaps, both scientific and cultural, between perception and reality, while celebrating the fascination, excitement and variety of desert lands and their inhabitants. Though generally seen as arid and infertile, deserts have been the birthplaces of critical evolutionary adaptations, civilizations, ideologies and agricultural and social progress. Deserts play active roles in the continued evolution of our climate and societies, demanding that we think seriously about these barren lands and their future. From scorching seas of sand to glacial polar expanses, Desert: Lands of Lost Borders relates the tales, truths, folklore and facts of the desert in an analysis that is at once informative and surprising. -- Jacket.
1. Wet and Dry, Hot and Cold --- 2. Big and Small, Fast and Slow--- 3. Insiders and Outsiders, Civilization and Strategy --- 4. Outsiders and Insiders, New World and Old --- 5. Mind and Matter, Body and Soul --- 6. Ancient and Modern, Boom and Bust --- 7. Barriers and Corridors, Imports and Exports --- 8. Feast or Famine, Knowns and Unknowns.
Includes bibliographical references (pages 372-389) and index.
Keywords: Deserts